The Function of Gondang Sabangunan in Ancestral Invocation Rituals - Kristina Samosir (Tradition and Modernity of Humanity, 2026)
Gondang Sabangunan in Batak Toba society is understood as a ritual medium used to call and bring the presence of ancestors into the human social space. The sound of gondang is not only used to accompany ceremonies but also acts as a symbolic action that opens cosmological communication, asks for blessings, and strengthens the relationship between descendants and ancestors. This research aims to analyze the practice of Gondang Sabangunan in the Batak Ancestors Educational Tourism Festival 2025 organized by the Rumahela community in Simullop, Pangururan. The study focuses on the ritual function of calling ancestors, the musical structure that supports the process, and the role of Dalihan Na Tolu relationships in organizing ritual participation. This research uses a qualitative method with a performance ethnography approach through participant observation, in depth interviews with musicians and cultural actors, and audiovisual documentation. The theoretical framework uses ritual music function theory from Alan P. Merriam, performance theory from Richard Schechner, and cultural behavior perspectives to understand sound as ritual action. The results show that stages such as requesting gondang, explaining ritual intentions, musical repetition patterns, and tortor participation form a symbolic process of calling ancestors that is still maintained in the festival context. The interaction of taganing as structural director, sarune bolon as symbolic vocal expression, and ogung as a marker of cosmological continuity creates a liminal condition that allows the experience of ancestor presence to be collectively felt. Although performed in a public space, the ritual practice does not fully lose its sacredness but transforms into a representational ritual that still contains spiritual meaning. Therefore, Gondang Sabangunan in the festival functions as a medium for spreading ritual knowledge and maintaining symbolic relationships between community and ancestors.